Pemanfaatan Limbah Gelas Plastik Sebagai Home Décor dalam Meningkatkan Kreativitas Masyarakat - Indriani, Susi; Wisdawati, Eka; Ashan, Muh. Dzulkifly; Syahiruddin, Muh.; Pajri, Pajri; Nugroho, Andy Ilham Widyanto (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The problem of plastic waste in Indonesia, especially plastic beverage glass waste, is increasing along with the growth of public consumption. Loka Village, Uluere District, Bantaeng Regency, as one of the agro-tourism areas in South Sulawesi, has also experienced an increase in the volume of plastic waste due to tourist visits. This community service activity aims to increase residents' awareness and creativity in managing plastic glass waste into aesthetically valuable home décor crafts. The implementation method includes initial observation, coordination and licensing with the village, socialization and education about the importance of plastic waste management, and demonstration of making recycled products. Evaluation was conducted through questionnaires to measure the increase in community creativity. The results of the service showed high enthusiasm from farm women, PKK, and PKL students. The community was able to understand the negative impact of plastic waste and showed increased creativity in utilizing waste into decorative products. This activity is expected to contribute to efforts to reduce plastic waste and develop an environment-based creative economy in Loka Hamlet.